Fenomena “Silent Reader” di Grup Kelas: Dampaknya Terhadap Komunikasi Akademik Mahasiswa - Rezy Wulan Mariani; Selfi Afrianti; Raisa Liani Putri; Qurratul Aini; Aulia Putri Azahara; Sal Sabillah Adi Putri; Mufida Aulia; Murni Fatmala Dewi Siagian; Hamdani Aidil Pratama; M. Diaz Aura Justin; Sulthanah Nashifah Dinnullah; Ere Mardella Arbiani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The silent reader phenomenon is one of the communication behaviors that is often found in students' online class groups. This behavior refers to individuals who read and follow information in a group, but never respond or actively engage in discussions. This study aims to analyze the phenomenon of silent readers in class groups and explore its impact on student academic communication. The method used is a literature study by examining various scientific sources that discuss digital communication, group interaction, and student behavior in online learning. The results showed that silent readers' behavior was influenced by internal factors such as low self-confidence, fear of making mistakes, and low motivation, as well as external factors such as social hierarchy, group communication culture, and information density in the group. This behavior has a negative impact on academic communication, including reduced two-way interaction, decreased quality of discussion, and inhibited collaboration between students. However, some students still get information through passive observation. Therefore, efforts are needed to create a more inclusive communication environment and encourage the active involvement of all group members so that academic communication can run more effectively.